Identification and Distribution of Sugarcane Stem Borer in Bangladesh - Rahman, Md Ataur; Noman, Md Shibly; Maleque, Md Abdul; Alam, Md Zinnatul; Afroz, Sultana; Chowdhury, MKA (SAARC Journal of Agriculture, 2014)
Field surveys were conducted during the cropping season of 2010-2011 to assess the distribution of Sugarcane stem borer species in 12 AEZs of Bangladesh. These surveys documented abundance and their distribution and results clearly showed the existence of the stem borer at all locations surveyed, but with a higher incidence in the Atwary (36%) and initiation of infestation was observed on 20 May. Stem borer incidence and distribution varied significantly among the different locations. Second highest rate of infestation (32%) was recorded in Bashudebpur followed by Dinajpur (31%), Pabna and Akandabaria farm (30%). The lower infestation was recorded in Kaliganj. The percentage of stems attacked at the Kaliganj has never exceeded 23% followed by Rajshahi (28%), Thakurgaon and Faridpur (29%). The rate of infestation of stem borer (Chilo tumidicostalis) in different locations varied from 23-36%. While morphological characteristics of stem borer species were identified with standard keys and species composition was only predominated by Chilo tumidicostalis Hampson, though previous workers found other borers in addition to this species. The sex ratio of adult moth Chilo tumidicostalis was 1:1.42 after emergence from the reared collected pupae from different locations. DOI: http://dx.doi.org/10.3329/sja.v11i2.18406 SAARC J. Agri., 11(2): 103-116 (2013)